Застосування аутологічної плазми, що збагачена тромбоцитами, для оптимізації репаративної регенерації кісткової тканини при остеопенії - Івченко, Дмитро Валерійович; Мірошніков, В. В.; Ивченко, Д. В.; Мирошников, В. В.; Ivchenko, D. V.; Miroshnikov, V. V. (Запорізький державний медичний університет, 2018)
Мета роботи – аналіз наукової літератури щодо ефективності застосування збагаченої тромбоцитарної плазми для оптимізації лікування компресійних переломів тіл грудних і поперекових хребців на тлі постменопаузального і сеніль¬ного остеопорозу. Усі способи застосування збагаченої тромбоцитами плазми, які описані в фаховій літературі, можна розділити на кілька основних груп. Так, вона може бути змішана з кістковим матеріалом, нанесена на осередок ушкоджен¬ня перед застосуванням кісткового матеріалу, нанесена поверх кісткового матеріалу, використана як біологічна мембрана. Збагачена тромбоцитами плазма містить фібрилярний і клітинний компоненти та здатна діяти як носій клітин, важливих для регенерації м’яких і кісткових тканин. Вона може посилювати прикріплення остеобластів людини до мембран і, як наслідок, індукувати остеогенез. Багато авторів є прихильниками стимулювального впливу плазми, що збагачена тромбоцитами, на репаративний остеогенез. Висновки. На основі відомостей фахової літератури показано високий потенціал терапії збагаченою тромбоцитами плазмою для регенерації кісткової тканини. Досі не виконали належних клінічних досліджень щодо ефективності терапії збагаченою тромбоцитами плазмою, які відповідали б усім сучасним критеріям. Терапія збагаченою тромбоцитами плазмою є перспективною галуззю в медицині та потребує наступних досліджень як новий ефективний і безпечний метод у лікарські практиці. Цель работы – анализ научной литературы об эффективности применения обогащенной тромбоцитами плазмы для оптимизации лечения компрессионных переломов тел позвонков грудной и поясничной локализации на фоне постменопаузального и сенильного остеопороза. Все способы применения обогащенной тромбоцитами плазмы, которые описаны в специализированной литературе, можно разделить на несколько основных групп. В частности, она может быть смешана с костным материалом, нанесена на очаг повреждения перед применением костного материала, нанесена поверх костного материала, использована в качестве биологической мембраны. Обогащенная тромбоцитами плазма содержит фибриллярный и клеточный компоненты и способна действовать как носитель клеток, важных для регенерации мягких и костных тканей. Она может усиливать прикрепление остеобластов человека к мембранам и, как следствие, индуцировать остеогенез. Многие авторы являются сторонниками стимули¬рующего воздействия плазмы, обогащенной тромбоцитами, на репаративный остеогенез. Выводы. На основании данных научной литературы показан высокий потенциал терапии плазмой, обогащенной тромбоцитами, для регенерации костной ткани. Не проведены надлежащие клинические исследования по эффек¬тивности обогащенной тромбоцитами плазмой терапии, которые отвечали бы всем современным критериям. Терапия обогащенной тромбоцитами плазмой – перспективная отрасль в медицине, заслуживает дальнейших исследований в плане нового эффективного и безопасного метода во врачебной практике. Objective: analysis of scientific literature on the effectiveness of using Plateled-Rich Plasma to optimize the treatment of compression fractures of vertebral bodies of thoracic and lumbar localization against the background of postmenopausal and senile osteoporosis. All the methods of using Platelet-Rich Plasma, described in the literature, can be divided into several main groups. Platelet- Rich Plasma can be mixed with bone material; is applied to the lesion site before application of bone material; is applied over the bone material; used as a biological membrane. Platelet-Rich Plasma contain fibrillar and cellular components and is able to act as a carrier of cells which are important for the regeneration of soft and bony tissues. It can strengthen the attachment of human osteoblasts to membranes and, as a consequence, induce osteogenesis. Many authors are the supporters of the stimulating effect of Platelet-Rich Plasma on reparative osteogenesis. After injection of Platelet-Rich Plasma in the case of complicated fracture the following was observed: odema in the damaged tissues is less pronounced, there are less signs of acute and chronic inflammation, the phase of alteration is changing more quickly by regenerative-reparative processes. The natural clot contains fibrin, fibronectin and vitronectin, they are also called adhesion molecules necessary for cell migration, osteoconduction, epithelialization and osseointegration. Biological properties of Platelet-Rich Plasma are due not only to the presence of growth factors (TGF-β and PDGF), but without them it immediately induces the formation of a fibrin clot, followed by stimulation of cell adhesion and collagen synthesis. Conclusion. Based on the published literature, a high potential of plasma therapy by Platelet-Rich Plasma for bone tissue regeneration is demonstrated. No adequate clinical studies on the effectiveness of Platelet-Rich Plasma therapy that would meet all modern criteria have yet been conducted. Therapy of Platelet-Rich Plasma is a promising branch in medicine and deserves further research in terms of new effective and safe method of application in medical practice.
Применение аутологичной плазмы, обогащенной тромбоцитами, для оптимизации репаративной регенерации костной ткани при остеопении
Autologous platelet-rich plasma application for the optimization of bone tissue reparative regeneration in osteopenia
Keywords: збагачена тромбоцитами плазма; кісткова регенерація; остеогенез; кісткове ремоделювання; мінеральний обмін; костное ремоделирование; обогащенная тромбоцитами плазма; костная регенерация; минеральный обмен; platelet-rich plasma; bone regeneration; osteogenesis; bone remodeling; mineral metabolism; osteoporosis